(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article contains the problem of defining the domain of Philosophy of Music in terms of understanding the essential purpose of Philosophy and Philosophizing. This work presents some general theses associated with the comprehension and the deployment of the fundamental aspects of music co-being. In particular, attempts to identify and highlight the subject area of study apart from the interdisciplinary nature of modern approaches to the study of the object of interest. First of all this is determined by the danger to start hard reductionism associated with the extensive and derived complex theories and methods on the way to the research of the music phenomenon. At the same time, there is another real danger of missing the metaphysical foundation amongst those particulars or, speaking in terms of Martin Heidegger, the “metaphysical roots» of «the sonorous». The main and most important part on the way of this research is the attempt to find the essential moments inside the music-being and their significance on the one hand, and a certain philosophical reflection on a more universal and fundamental level, on the other. Thus, determination of the domain occurs deep both into the music nature and the human existence at the same time. Keywords: philosophy, being, existence, music, man (person), spiritual production, culture, creativity.